Thermohydraulic management coupled with flow pattern distinction for concentrating solar direct-steam-generation technology. (March 2023) - Wang, Yongqing; Guo, Zhenning; Li, Lu; Gao, Fan; Wang, Ke; An, Bo
Abstract: Concentrating solar direct-steam-generation (DSG) technology is favored for tying solar energy and water to directly power the energy loop, which is positive in achieving a zero-carbon future. Whereas, the external intermittence of the meteorological irradiation and internal instability of flow boiling pose challenges to the thermohydraulic operation and management. Herein, a light-heat-flow-pattern transient coupled analysis model of parabolic trough collector direct-steam-generation (PTC-DSG) loop was established to figure out the action among the irradiance, thermohydraulic and two-phase flow pattern. The transient flow patterns along the loop were investigated under different irradiance ( I ), mass flowrate ( m in ) and inlet temperature ( t in ) of the loop. The results showed that increasing I and t in temporarily reduces the probability of stratified flow and increasing t in permanently reduces the probability of stratified flow. In all cases, the proportion of intermittent flow to evaporation stage remains almost unchanged (about 11%.), and the heat transfer in superheating stage still needs a long time (253s ∼ 3646s) to recover after the flow stages distribution is stable. More importantly, a quantified management strategy for irradiance -thermohydraulic-flow pattern is built. To achieve a favorable operating state, the inlet mass flow rate m in should be lower than the superheated line ((1.25· I – 6.25)✕10 −3 kg s −1 ) to obtain the superheated steam, and higher than 0.35 kg s −1 to get out of the stratified flow in evaporation stage. When the irradiation is lower than 285 W m −2 for a long time, the start-up and operation is not recommended. Graphical abstract: Image 1